ADBIS, TPDL and EDA 2020 Common Workshops and Doctoral Consortium : International Workshops: DOING, MADEISD, SKG, BBIGAP, SIMPDA, AIMinScience 2020 and Doctoral Consortium, Lyon, France, August 25-27, 2020, Proceedings /: International Workshops: DOING, MADEISD, SKG, BBIGAP, SIMPDA, AIMinScience 2020 and Doctoral Consortium, Lyon, France, August 25-27, 2020, Proceedings. ([2020]) - Unknown
No abstract available